Sequential Vertical Integration - Quirmbach, H. C. (Quarterly Journal of Economics, 1992)
Journal Article Sequential Vertical Integration Get access Herman C. Quirmbach Herman C. Quirmbach Iowa State University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 107, Issue 3, August 1992, Pages 1101–1111, https://doi.org/10.2307/2118377 Published: 01 August 1992